Red Star falling - Berry, Steve, 1955-; Blackwood, Grant (Berry, Steve, 1955- Luke Daniels thriller, 2024)
Wrapping up his latest assignment for the Magellan Billet, Luke Daniels receives a surprise visit from the head of a former-CIA operation named Sommerhaus -- a failed attempt to assemble an espionage network within the Ukraine on the eve of the Russian invasion. Sommerhaus ranks high on Luke's list of painful regrets for it was during this mission that his friend, CIA case officer John Vince, was captured by Russian operatives and supposedly executed. But Luke is provided some shocking news. Vince is alive, in failing health, locked behind the walls of Russia's brutal Solovetsky Island prison, and has a critical message he'll give to no one but Luke. Needing no further convincing Luke vows to bring Vince home. However, just as he manages to extract his friend from prison Vince tragically dies and his final words are rambling and incoherent. Just bits and pieces. But enough to plunge Luke into a hunt for something lost since the 15th century. The legendary library of the first Tsar of All Russia, Ivan the Terrible. Within that priceless collection of rare manuscripts is the key to unraveling a modern-day cipher and stopping a secret Soviet satellite program that still exists. But Luke is not the only one on the trail. Others, both inside and out of Russia, want the library for a totally different reason -- to re-start the Red Star program and finally unleash its destructive potential. Luke's mission is clear. Find the lost library, solve the puzzle, and prevent Red Star falling.